The Role of Public Speaking Skills in Improving the Performance of Hajj Guides - Desi Hasbiyah; Rofiah; Asep Gunawan; Falizar Rivani; Tohir Solehudin (JPG: Jurnal Pendidikan Guru, 2025)
This study explores the crucial role of public speaking skills in enhancing the effectiveness of Hajj guidance. As part of 21st-century competencies, public speaking not only facilitates communication but also serves as a strategic tool for delivering religious messages in a compelling and meaningful manner. In the context of Hajj guidance, strong public speaking skills help build confidence, reinforce authority, and prevent miscommunication. Through a literature review, this article examines key components of public speaking such as interpersonal communication, credibility of hajj pilgrimage guide as a speaker, content mastery, and the application of public communication psychology. The findings suggest that well-developed public speaking skills can improve communication effectiveness, support spiritual development, and contribute to a smooth and solemn Hajj experience.